NCL: Storing ambient settings in media node - Barreto, Fabio; Montevecchi, Eyre Brasil B.; Abreu, Raphael; Santos, Joel A. F. dos; Muchaluat-Saade, Debora C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
This proposal consists of adding one more type of variable storage setting node, called “x-ncl-ambient-settings,” which stores environment information. This information may come from sensors in the physical ambient that must update this data periodically or as defined by the author of the NCL document. These variables can be used by NCL links or procedural code to drive application behavior based on the perceived environment information.